2008
DOI: 10.1115/1.2900724
|View full text |Cite
|
Sign up to set email alerts
|

PIV-Measured Versus CFD-Predicted Flow Dynamics in Anatomically Realistic Cerebral Aneurysm Models

Abstract: Computational fluid dynamics (CFD) modeling of nominally patient-specific cerebral aneurysms is increasingly being used as a research tool to further understand the development, prognosis, and treatment of brain aneurysms. We have previously developed virtual angiography to indirectly validate CFD-predicted gross flow dynamics against the routinely acquired digital subtraction angiograms. Toward a more direct validation, here we compare detailed, CFD-predicted velocity fields against those measured using parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(114 citation statements)
references
References 33 publications
5
108
0
1
Order By: Relevance
“…While 3D PC-MRA correlates well with laser Doppler velocimetry in straight arteries, intra-aneurysmal flows are frequently slow and highly disturbed; in such regions, obtaining a high signal intensityto-noise ratio is difficult. 16 Ford et al 17 found that pulsatile intra-aneurysmal hemodynamics obtained from CFD captured the gross and finer flow details compared with particleimage velocimetry.…”
Section: Discussionmentioning
confidence: 99%
“…While 3D PC-MRA correlates well with laser Doppler velocimetry in straight arteries, intra-aneurysmal flows are frequently slow and highly disturbed; in such regions, obtaining a high signal intensityto-noise ratio is difficult. 16 Ford et al 17 found that pulsatile intra-aneurysmal hemodynamics obtained from CFD captured the gross and finer flow details compared with particleimage velocimetry.…”
Section: Discussionmentioning
confidence: 99%
“…Although the main hemodynamic features are thought to be preserved, 32 these simplifications may cause differences between the results of CFD simulation and the in vivo state. Specifically, the present CFD study has the following limitations: First, single vascular geometry was examined.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Waveforms are usually obtained from population-averaged measurements taken on healthy volunteers. 14,43 While the use of such waveforms remains the most popular method of BC application (17 out of 18 non-patient-specific BCs in our review), the method carries important limitations. First, as these measurements are taken in a healthy population, they may not be representative of patient waveforms.…”
Section: Non-patient-specific Bcmentioning
confidence: 99%